Ultrasound-assisted Maillard reaction for the preparation of whey protein-fructooligosaccharide conjugates - Singh, Pallavi; Roy, Anirban; Kundu, Aditi; Mondal, Firoz; Sarkar, Mehulee; Saha, Supradip (Frontiers in Nutrition, 2025)
The current study investigated the effect of ultrasonication treatment on the conjugation of whey protein concentrate (WPC) with fructooligosaccharides (FOS) via the Maillard reaction (MR). The degree of glycation (DG) was evaluated by assessing the loss of amino groups using the o-phthaldialdehyde (OPA) method, and Maillard-type conjugation was confirmed through Fourier-transform infrared spectroscopy (FTIR) and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Ultrasonication significantly accelerated the glycation reaction, achieving a glycation degree of 49.6% in just 60 min, compared to 12.4% over 16 h with conventional heating. This method produced Maillard-type conjugates with reduced browning intensity and improved, controlled protein solubility at acidic pH with higher oligosaccharide ratios, offering valuable potential for protein delivery applications. Furthermore, response surface methodology (RSM) was used for optimizing the Maillard reaction (MR) conditions for WPC and FOS.